Multiplicación vegetativa in situ de canela (Cinnamomun zeylanicum) mediante hormona enraizadora en acodos aéreos - Velastegui Vargas, Jorge Neptali (2011)
Cinnamon, also known as (cinnamon, cinnamon of India) is grown in our east and is used for many years in the culinary arts and palmist. Eastern climatic conditions are favorable for this crop. This research was conducted at the "Tello" in Barrio Los Angeles belongs to the district and province of Pastaza, whose geographical coordinates are 1 ° 20 'south latitude and 77 º 15' west longitude. The research work lasted 120 days and main objective was to determine the effect of the hormone NAA (naphthalene acetic acid) in the rooting of cinnamon applied in air layering. The treatments used in this research are: T1 = no hormone (Control), T2 = 5000 mg kg -1 of ANA, T3 = 6000 mg kg -1 NAA and T4 = 7000 mg kg -1 of NAA. We used a completely randomized design (DCA) measurements were made the following trips: Percentage of rooting (%) maximum root length (mm) Number of roots and roots diameter (mm), also performed the analysis economic treatment, which was used for the benefit / cost. The results were: In 88 days of experiment, treatment 6000 mg kg -1 of NAA showed the highest number of roots (15), 10.20 cm root length and stem diameter of 1.09 cm. In the 104 days of treatment 6000 mg kg -1 of ANA reported the best result in number of roots (18), root length (13.68 mm) and stem diameter (1.22 mm). At the end of the trial (120 days), 6000 mg kg -1 treatment of ANA reported the highest average number of roots (42), root length (18.68 mm) and roots diameter (1.22 mm). Treatment 6000 mg kg -1 of NAA showed the highest percentages of rooting 29.60, 36.00 and 83.20% in the order of each research phase. The highest net benefit and the benefit / cost were to the control treatment and 0.44 to 61.10 dollars.